2017
DOI: 10.1111/jnu.12338
|View full text |Cite
|
Sign up to set email alerts
|

Call to Action: The Case for Advancing Disaster Nursing Education in the United States

Abstract: Opportunities exist to strengthen disaster readiness and enhance national health security by expanding educational programming and training for nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 31 publications
1
38
0
1
Order By: Relevance
“…The authors examined disaster preparedness in emergency nurses' levels of awareness, knowledge, skills and perceptions of emergency nurses in Mecca with regard to mass gathering disaster. The findings from this study support previous research that suggested that despite the substantial experience gained through clinical engagement in prior mass casualties, there is a deficit in knowledge of the major incident plans for emergency nurses working in public hospitals (Alzahrani & Kyratsis, 2017 Disaster nursing is a specialty and can be defined as the adaptation of professional nursing skills in recognizing and meeting the nursing physical and emotional needs resulting from a disaster (Veenema et al, 2017b). The overall goal of disaster nursing is to achieve the best possible level of health for the people and the community involved in the disaster (Veenema et al).…”
Section: Disaster Definition Scope and Managementsupporting
confidence: 83%
See 1 more Smart Citation
“…The authors examined disaster preparedness in emergency nurses' levels of awareness, knowledge, skills and perceptions of emergency nurses in Mecca with regard to mass gathering disaster. The findings from this study support previous research that suggested that despite the substantial experience gained through clinical engagement in prior mass casualties, there is a deficit in knowledge of the major incident plans for emergency nurses working in public hospitals (Alzahrani & Kyratsis, 2017 Disaster nursing is a specialty and can be defined as the adaptation of professional nursing skills in recognizing and meeting the nursing physical and emotional needs resulting from a disaster (Veenema et al, 2017b). The overall goal of disaster nursing is to achieve the best possible level of health for the people and the community involved in the disaster (Veenema et al).…”
Section: Disaster Definition Scope and Managementsupporting
confidence: 83%
“…Next, the recommendations and implications for advanced nursing practice will be presented. appropriate manner (Veenema et al, 2017b). Serious consideration needs to be given to building core disaster concepts into undergraduate and graduate level nursing programs.…”
Section: Preparedness Information Retrospective (Epiq)mentioning
confidence: 99%
“…• Education for health care professionals on environmental sustainability should include o general knowledge about the climate crisis effects on population health, including 10,11 ▪ air pollution, ▪ exposure to toxins, ▪ heat-related illnesses, 10,11 ▪ extreme weather events, 10,11 ▪ physical and mental health effects of natural disasters, 12 ▪ need for reliable access to clean food and water, and ▪ modification of vector-borne, zoonotic, and waterborne diseases 13 ; o disaster preparedness 10 ; o health system infrastructure resilience [14][15][16][17] ; o supply chain engagement 18 ; o financial, social, and environmental benefits of environmental best practices 19 ; and o real-world examples of environmental best practices in health care services. • Environmentally responsible decision-making in health care delivery should align with local, state and federal regulations and support patient safety and optimal clinical outcomes.…”
Section: Position Statementmentioning
confidence: 99%
“…Finally, in considering the preparedness of front-line healthcare professionals to effectively respond to disasters, two common issues have surfaced. First, although nurses represent the largest group of the healthcare workforce and are at the forefront of the healthcare response to disasters, findings from assessments of professional readiness indicate that many of the nation's nurses are ill-prepared to respond to the complex demands of disasters (Veenema et al, 2017). Second, healthcare professionals, including nurses, who desire to travel across state lines to provide assistance in other jurisdictions, often face barriers in getting their credentials verified in a timely manner to allow them to quickly respond to disaster-stricken areas where their expertise and skills are in high demand.…”
Section: Introductionmentioning
confidence: 99%